2018
DOI: 10.1007/s11095-018-2402-9
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modeling to Describe the Total Plasma and Free Brain Levels of Fluconazole in Healthy and Cryptococcus neoformans Infected Rats: How Does the Infection Impact the Drug’s Levels on Biophase?

Abstract: FLC showed a limited use in monotherapy to the treatment of criptoccocosis in rats and humans to value of MIC >8 μg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Fluconazole is well known to have linear pharmacokinetics [11, 16–18]. For this reason, we used a linear regression model for predicting the plasma concentrations following oral fluconazole at 100 mg, 200 mg, 400 mg, 1200 mg, 1600 mg, and 2000 mg/day from the measured concentrations following oral fluconazole 800 mg daily given as directly observed therapy while hospitalized [15, 19].…”
Section: Methodsmentioning
confidence: 99%
“…Fluconazole is well known to have linear pharmacokinetics [11, 16–18]. For this reason, we used a linear regression model for predicting the plasma concentrations following oral fluconazole at 100 mg, 200 mg, 400 mg, 1200 mg, 1600 mg, and 2000 mg/day from the measured concentrations following oral fluconazole 800 mg daily given as directly observed therapy while hospitalized [15, 19].…”
Section: Methodsmentioning
confidence: 99%
“…This study demonstrated that the infection was able to alter the distribution of FLZ in the brain of infected animals. Furthermore, this study shows that when used in monotherapy, FLZ is of limited use in monotherapy to the treatment of cryptococcosis in rats and humans to a value of MIC >8 μg/mL (Alves et al, 2018). Stott et al, (2018) came to a similar conclusion, after investigating the impact of a series of clinically relevant covariates on the penetration of FLZ into the CNS in adults with cryptococcal meningitis, after oral doses of 800 mg every 24 h in combination with AmB deoxycholate at a dose of 1 mg/day.…”
Section: Fluconazolementioning
confidence: 87%
“…FLZ is a synthetic triazole antifungal used in the treatment of cryptococcal meningoencephalitis and there are countries where it is the only available drug for treating these infections (Sudan et al, 2013;Wang et al, 2017). FLZ is recommended as the main therapeutic agent for the maintenance phase of cryptococcal meningoencephalitis, it has a safety profile, low toxicity, long half-life, physicochemical characteristics that carry on good tissue distribution, is orally bioavailable, has excellent CNS penetration, and has a linear PK (Wang et al, 2017;Santos et al, 2016;Alves et al, 2018;Hope et al, 2019).…”
Section: Fluconazolementioning
confidence: 99%
See 1 more Smart Citation
“…However, on a fixed regimen of antifungal therapy, PK results are variable, and such levels can be quantified by population PK modeling. Monte Carlo simulation is a useful tool in replicating pharmacokinetic variability [ 162 ]. For example, the role of fluconazole is to inhibit growth, not to kill.…”
Section: Role Of Pk/pd Levelsmentioning
confidence: 99%